Media of reason : a theory of rationality - Vogel, Matthias (New directions in critical theory., 2012)
Matthias Vogel challenges the belief, promoted by many contemporary philosophers, that reason is determined solely by our discursive, linguistic abilities as communicative beings. In his view, the medium of language is not the only force of reason?music, art, and other nonlinguistic forms of communication and understanding are also significant factors. Introducing an expansive theory of the mind that accounts for highly sophisticated, penetrative media, Vogel advances a novel conception of rationality while freeing philosophy from its attachment to linguistics. Vogel's media of rat.